Introspection into Institutional Database Allows for Focused Quality Improvement Plan in Cardiac Surgery: Example for a New Global Healthcare System. Issue 10 (October 2013) - Lancaster, Elizabeth; Postel, Mackenzie; Satou, Nancy; Shemin, Richard; Benharash, Peyman
Reducing readmission rates is vital to improving quality of care and reducing healthcare costs. In accordance with the Patient Protection and Affordable Care Act, Medicare will cut payments to hospitals with high 30-day readmission rates. We retrospectively reviewed an institutional database to identify risk factors predisposing adult cardiac surgery patients to rehospitalization within 30 days of discharge. Of 2302 adult cardiac surgery patients within the study period from 2008 to 2011, a total of 218 patients (9.5%) were readmitted within 30 days. Factors found to be significant predictors of readmission were nonwhite race ( P = 0.003), government health insurance ( P = 0.02), ejection fraction less than 40 per cent ( P = 0.001), chronic lung disease ( P < 0.001), and hospital length of stay greater than 7 days ( P = 0.02). Patients undergoing aortic and mitral valve operations had an increased risk of readmission compared with other cardiac operations ( P < 0.001). The most common reasons for rehospitalization were pneumonia and other respiratory complications (n = 27 [12.4%]). Recognition of risk factors is crucial to reducing readmissions and improving patient care. Our data suggest that optimizing cardiopulmonary status in patients with comorbidities such as heart failure and chronic obstructive pulmonary disease, increasing directed pneumonia prophylaxis, patient education tailored to specific patient social needs, earlier patient follow-up, and better communication between inpatient and outpatient physicians may reduce readmission rates.